Let's first find the time the object takes to reach the maximum height from the kinematic equation:
"v=v_0-gt,""0=v_0-gt,""t=\\dfrac{v_0}{g}."Then, we can substitute "t" into another kinematic equation and find "y_{max}":
"y_{max}=v_0t-\\dfrac{1}{2}gt^2,""y_{max}=v_0\\dfrac{v_0}{g}-\\dfrac{1}{2}g(\\dfrac{v_0}{g})^2,""y_{max}=\\dfrac{v_0^2}{2g}=\\dfrac{(60\\ \\dfrac{m}{s})^2}{2\\cdot 9.8\\ \\dfrac{m}{s^2}}=183.7\\ m."Finally, we can find the time the object takes to reach the maximum height:
"t=\\dfrac{v_0}{g}=\\dfrac{60\\ \\dfrac{m}{s}}{9.8\\ \\dfrac{m}{s^2}}=6.1\\ s."Answer:
"y_{max}=183.7\\ m, t=6.1\\ s."
Comments
Leave a comment